2002
DOI: 10.4269/ajtmh.2002.67.273
|View full text |Cite
|
Sign up to set email alerts
|

Activity of azithromycin against Leishmania major in vitro and in vivo.

Abstract: Abstract. Azithromycin, an azalide antibiotic of the macrolide family, concentrates in the tissues and especially in macrophages. Because Leishmania parasites reside in these cells, we tested this antibiotic for a possible antileishmanial activity in vitro and in vivo. Azithromycin decreased the Leishmania major promastigote count in cell-free cultures at log phase approximately 50-fold. In macrophage cultures infected with L. major amastigotes, azithromycin caused a significant decrease in parasite levels wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 31 publications
3
27
0
4
Order By: Relevance
“…In an experiment in-vitro and in-vivo model, azithromycin showed activity against Leishmania major (KROLEWIECKI et al, 2002). In an open trial in Brazil, it cured 16 out of 20 patients with cutaneous ulcers caused by Leishmania (Viannia) braziliensis, however, cure time, doses and cycles number presented high variability (PRATA et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In an experiment in-vitro and in-vivo model, azithromycin showed activity against Leishmania major (KROLEWIECKI et al, 2002). In an open trial in Brazil, it cured 16 out of 20 patients with cutaneous ulcers caused by Leishmania (Viannia) braziliensis, however, cure time, doses and cycles number presented high variability (PRATA et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As it concentrates in tissues and especially in macrophages, and may reach levels 100 to 200 times higher than those in serum (Gladue et al 1989) therefore, its potential role as antileishmanial agent was evaluated. Krolewiecki et al (2002) demonstrated that, azithromycin has antileishmanial activity following its subcutaneous adminstration in BALB\c mice infected with Leishmania major. Moreover, Sinagra et al (2007) reported significant activity of its oral adminstration against Leishmania (Viannia) braziliensis however, no activity against infections with Leishmania (Leishmania) amazonensis in golden hamsters could be observed.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] A classe dos macrolídeos atua inibindo a síntese proteica, dissociando o peptídio do ribossomo. 6 Tem características como a de concentrarse nos tecidos, especialmente nos macrófagos, com níveis 100 a 200 vezes superiores do que no soro, tornando-a atrativa para o tratamento de infecções causadas por micro-organismos intracelulares.…”
Section: Introductionunclassified
“…Usando-a no tratamento de pacientes, foi demonstrada ação leishmaniostática com resposta terapêutica mais lenta do que a dos antimoniais. 5 Em experimentações in vitro, a azitromicina não contribuiu para a fagocitose da L. major, mas aumentou a taxa de morte intracelular das amastigotas. 8 Outra possibilidade é que a azitromicina tenha efeito imunomodulador, diminuindo-lhes o número e ativando neutrófilos e prevenindo a produção de mediadores e citocinas pró-inflamatórias.…”
Section: Introductionunclassified
See 1 more Smart Citation